Environment in question : ethics and global issues / edited by David E. Cooper and Joy A. Palmer - Cooper, David E.; Palmer, Joy A. (ed.) (London, 1992)
The growth in the study of environmental issues has left many people struggling to find their way around an increasingly complex area. This book supplies the reader, in a single volume, with an introduction to key debates, providing both practical and theoretical knowledge. It presents information on specific environmental issues and outlines the arguments and ethical problems that have developed in and around such issues. The contributors take a global perspective, reflected in contributions from the UK, USA, India and Australia. They represent a variety of disciplines, including geography, environmental science, psychology and philosophy, and incorporate a number of approaches, from discussion on the disposal of nuclear waste to consideration of our debt to future generations.
Keywords: Human ecology-moral and ethnical aspects